If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(n + -2) = 5(n + 3) Reorder the terms: 4(-2 + n) = 5(n + 3) (-2 * 4 + n * 4) = 5(n + 3) (-8 + 4n) = 5(n + 3) Reorder the terms: -8 + 4n = 5(3 + n) -8 + 4n = (3 * 5 + n * 5) -8 + 4n = (15 + 5n) Solving -8 + 4n = 15 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -8 + 4n + -5n = 15 + 5n + -5n Combine like terms: 4n + -5n = -1n -8 + -1n = 15 + 5n + -5n Combine like terms: 5n + -5n = 0 -8 + -1n = 15 + 0 -8 + -1n = 15 Add '8' to each side of the equation. -8 + 8 + -1n = 15 + 8 Combine like terms: -8 + 8 = 0 0 + -1n = 15 + 8 -1n = 15 + 8 Combine like terms: 15 + 8 = 23 -1n = 23 Divide each side by '-1'. n = -23 Simplifying n = -23
| n^2-11n+18=0 | | -(7y+5)-(6y-8)=3 | | 5(x+4)-(3x-4)= | | 9n^2+81n= | | 3(u+1)(u-1)=0 | | b^2-9b-10=0 | | np=63 | | 3(u-1)(u+1)=0 | | 0.4x+0.25(132-x)=27 | | 4x+x+-6x=5 | | x-13=34 | | 9(w+4)=6(w-3) | | n^2+7p-18=0 | | 0.4x+.25(144-x)=37 | | -15=9-6x | | 3-3u^2=0 | | 4(x-7)=2(x+7) | | 15=-3-2x | | -19=5-8x | | 2(3n+2)=7(3n+3)+5 | | 4900=x^2+48x | | -15=3-9x | | -16=10-2x | | -5x^2-3x+2=0 | | -17=5+2x | | -2-2x=-12 | | -14=4-6x | | -5+5x=-15 | | 4(h+3)=2(-2h-14) | | 3+10x=-17 | | -4+3x=-10 | | 0.25t+0.25(t+16)=4+0.75t |